Kajian Perilaku Pengguna Taman Kota di Kabupaten Blitar - Astuti, Etika Dwi Kusuma; Winarsih, Erna; Budiyanto, Hery (VISA: Journal of Vision and Ideas, 2025)
The existence of city parks can be utilized to improve the quality of the environment and social relations of the community. Social relations of the community can be seen from the interaction between individuals in using space that forms behavioral patterns. Thus, the development of city parks can be seen from the behavior of the people who use them. Kanigoro Park is a city park located in Blitar district with different levels of visitor activity. To find out the problems and influence of city park elements on visitor behavior, it is necessary to conduct research on the behavior of city park users in Kanigoro Park. The purpose of this study is to identify the behavior of city park users as a public space. The methods used in this study are qualitative descriptive methods and behavior mapping methods. Behavior mapping is used to determine the movement patterns of city park users using the place-centered mapping technique. The results of this research concluded that shaded spaces are an element that greatly influences visitor activities because there are many activities carried out in this zone. Kanigoro Park is a park that is quite large so that it creates high activity patterns, making it a strong factor in forming visitor behavior patterns in social interaction.